F-SIGNATURE UNDER BIRATIONAL MORPHISMS. (17th April 2019) - MA, LINQUAN; POLSTRA, THOMAS; SCHWEDE, KARL; TUCKER, KEVIN
Abstract : We study F -signature under proper birational morphisms [STIX]x1D70B:Y→ X, showing that F -signature strictly increases for small morphisms or if K_Y[STIX]x1D70B^* K_X . In certain cases, we can even show that the F -signature of Y is at least twice as that of X . We also provide examples of F -signature dropping and Hilbert–Kunz multiplicity increasing under birational maps without these hypotheses.